2015
DOI: 10.1007/s12517-015-1982-5
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of sands along the Ain Soukhna and Ras Gharib beaches, Gulf of Suez, Egypt: implications for provenance and tectonic setting

Abstract: Provenance, tectonic setting, and weathering condition of sands from the Ain Soukhna (AS) and Ras Gharib (RG) beaches along the Gulf of Suez, Egypt, have been studied using mineralogy and major and trace element data. The textural study reveals that the proportion of quartz is higher in RG (65-81 %) than in AS (47-54 %) sands. The compositional similarity between the AS and RG sands is tested statistically by the application of analysis of variance (ANOVA) at 95 % confidence level to avoid misinterpretation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…This implies a passive margin that reflects the geology of the western coast of Ghana. In all, the findings of this study can be compared to similar studies in coastal areas across the globe especially in the Gulf of Suez, Egypt (Zaid, 2015), Baja California Peninsula, Mexico (Kasper-Zubillaga and Zolezzi-Ruiz, 2007), Gulf of Mexico (Kasper-Zubillaga et al, 1999;Armstrong-Altrin, 2009Armstrong-Altrin et al, 2012Hernandez-Hinojosa et al, 2018), Tanjero Formation around Arbat, northeastern Iraq (Çelik and Salih, 2018), and Lake Hazar, Elazığ, Eastern Turkey (Akkoca et al, 2019). All these studies point to the activities of continental rifting as the main precursor to sediment rafting from source rocks and deposition of beach sands as in the case of the western coast of Ghana.…”
Section: Tectonic Settingmentioning
confidence: 60%
See 1 more Smart Citation
“…This implies a passive margin that reflects the geology of the western coast of Ghana. In all, the findings of this study can be compared to similar studies in coastal areas across the globe especially in the Gulf of Suez, Egypt (Zaid, 2015), Baja California Peninsula, Mexico (Kasper-Zubillaga and Zolezzi-Ruiz, 2007), Gulf of Mexico (Kasper-Zubillaga et al, 1999;Armstrong-Altrin, 2009Armstrong-Altrin et al, 2012Hernandez-Hinojosa et al, 2018), Tanjero Formation around Arbat, northeastern Iraq (Çelik and Salih, 2018), and Lake Hazar, Elazığ, Eastern Turkey (Akkoca et al, 2019). All these studies point to the activities of continental rifting as the main precursor to sediment rafting from source rocks and deposition of beach sands as in the case of the western coast of Ghana.…”
Section: Tectonic Settingmentioning
confidence: 60%
“…Major element tectonic discrimination diagrams of Bhattia (1983) and Roser and Korsch (1986) are widely used in sediment provenance studies (e.g., Valloni and Maynard, 1981;Dostal and Keppie, 2009;Tobia and Aswad, 2015 Armstrong-Altrin (2015) interpreted the two tectonic discrimination diagrams and suggested that they can be used as effective guides for discriminating the tectonic setting of paleosedimentary basins. Following this, the two new proposed tectonic discrimination diagrams have been effectively used in several studies to discriminate the tectonic environment of sediment sources using their geochemistry (e.g., Guadagnin et al, 2015;Tawfik et al, 2015;Zaid et al, 2015). On these diagrams, the studied samples plot entirely within rifted setting in the high silica tectonic discrimination diagram (Figure 9a) whereas on the low silica tectonic diagram (Figure 9b), they plot at the transition between the collision setting and rifted tectonic setting although they are much closer to the rifted setting.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…A statistically significant correlation observed between SiO 2 and Al 2 O 3 indicating that much of SiO 2 is not present as quartz grains (Awadh & Al‐Ankaz, ; Schneider, Hornung, Hinderer, & Garzanti, ). Similarly, a significant correlation of K 2 O versus Al 2 O 3 , Ba, and Rb is suggesting that K, Rb, and Ba are likely hosted in K‐feldspar (Zaid, , ). The correlation of Co, Cr, Sc, and V versus Al 2 O 3 is not significant, which probably suggests the association of these elements with accessory minerals (Armstrong‐Altrin, Lee, Kasper‐Zubillaga, & Trejo‐Ramírez, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these discrimination diagrams were successfully used in recent studies to discriminate the tectonic setting of a source region based on the geochemistry of clastic sediments (e.g., Armstrong-Altrin & Machain-Castillo, 2016;Guadagnin et al, 2015;Nagarajan et al, 2015;Tawfik et al, 2017;Zaid, 2015aZaid, , 2015bZaid, , 2015c. On these high sil-…”
Section: Tectonic Settingmentioning
confidence: 99%
“…The composition of siliciclastic sediments is controlled by several factors, such as the nature of the parent rocks, intensity of weathering, paleoclimate, distance of transport, grain size, hydraulic sorting, and post‐depositional modifications (Johnsson & Basu, ; McLennan, Hemming, McDaniel, & Hanson, ). The petrography and geochemistry of siliciclastic sediments have been widely used to identify the provenance (e.g., Armstrong‐Altrin et al, ; Maravelis & Zelilidis, ; Odoma, Obaje, Omada, Idakwo, & Erbacher, ; Tawfik, Ghandour, Maejima, Armstrong‐Altrin, & Abdel‐Hameed, ; Zaid, , ), evaluate the weathering history of the source area (Madhavaraju & Ramasamy, ; Rahman, Sayem, & McCann, ; Tao, Sun, Wang, Yang, & Jiang, ; Tawfik, Ghandour, Maejima, & Abdel‐Hameed, ), deduce the tectonic setting and depositional environment (Armstrong‐Altrin, ; Etemad‐Saeed et al, ; Etemad‐Saeed, Hosseini‐Barzi, Adabi, Sadeghi, & Houshmandzadeh, ; Gideon, Fatoye, & Omada, ; Mishra & Sen, ; Tawfik, Ghandour, Maejima, & Abdel‐Hameed, ; Verma & Armstrong‐Altrin, ; Verma, Díaz‐González, & Armstrong‐Altrin, ; Zhou, Friis, & Poulsen, ), and to interpret the post‐depositional changes (Ghandour, Al‐Washmi, Bantan, & Gadallah, ; Zaid, ; Zaid & Gahtani, ).…”
Section: Introductionmentioning
confidence: 99%